Central serous chorioretinopathy after blunt trauma. (28th May 2012) - Ponce, Claudia Maria Prospero; Mohidat, Hasan M; Garcia, Charles A
Abstract : The authors report a case of a 46-year-old Hispanic male with central serous chorioretinopathy (CSC) following blunt trauma to the left eye. The patient presented with a complaint of throbbing headache and blurry vision in left eye. The patient was diagnosed with diabetes mellitus 1 year previous to the event. On examination, uncorrected visual acuity was 20/20 OD, 20/200 OS. No anisocoria or afferent pupillary defect was present. Intraocular pressure was normal. Subconjunctival haemorrhage and lid ecchymosis were present in OS and fundus examination showed serous macular detachment and central retinal pigment epithelium detachment, and no evidence of diabetic retinopathy. Optical coherence tomography OS showed subretinal fluid and fluorescein angiography demonstrated the typical 'smokestack' pattern of leakage into the subretinal space. The patient received observational therapy for 4 months and the CSC spontaneously resolved with visual acuity of 20/20 in left eye.